(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Globalization is the process of international interaction and integration through exchanges of views, products, ideas and various aspects of culture. It is a fact that many skill and competencies of physicians are universal, as well as the required patient management skills are similar throughout the world. However, medical curriculum differs greatly worldwide in their content, thus, levels of professional competences acquired by graduates of medical schools varies across the globe. Consequently, it becomes difficult to get uniform global physician. Therefore, the concept of global physician to become a reality, it is necessary to determine a set of core competencies that define what a physician is, regardless of where he or she has been educated. Globalization in medical education is a dynamic process. If any medical graduate does not want to remain confined within his or her own locality he or she has to customize him or herself according to the necessity of the globe. Thus, introduction of globally standardized uniform medical education curriculum is essential for everybody. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 37-42